Uma sequência didática para o ensino de transformações geométricas com o GeoGebra - Pimentel, Luiz Fernando Garcia (2016)
This actual study is an investigation about the importance of using computers and other information and communication technologies (ICTs) in the teaching of Mathematics. We believe in the thesis that ICT can contribute as an educational means for the improvement of teaching and learning situations, and consequently in solving problems such as school failure and school indiscipline. Therefore, we designed and applied a didactic sequence using the Geogebra for the development of Isometries topic in a class of 6th grade of elementary school. The didactic sequence was structured within the perspectives of Didactic Engineering and adopted a qualitative methodology. The results indicate that ICTs contribute significantly in the process of teaching and learning, but some external factors are still obstacles to the effective implementation of this resource in schools.